Direct conscious telemetry recordings demonstrate increased renal sympathetic nerve activity in rats with chronic kidney disease - Salman, Ibrahim M.; Kandukuri, Divya S.; Harrison, Joanne L.; Hildreth, Cara M.; Phillips, Jacqueline K. (Frontiers in Physiology, 2015)
Chronic kidney disease (CKD) is associated with sympathetic hyperactivity and impaired blood pressure control reflex responses, yet direct evidence demonstrating these features of autonomic dysfunction in conscious animals is still lacking. Here we measured renal sympathetic nerve activity (RSNA) and mean arterial pressure (MAP) using telemetry-based recordings in a rat model of CKD, the Lewis Polycystic Kidney (LPK) rat, and assessed responses to chemoreflex activation and acute stress. Male LPK and Lewis control animals (total n=16) were instrumented for telemetric recording of RSNA and MAP. At 12–13 weeks-of-age, resting RSNA and MAP, sympathetic and haemodynamic responses to both peripheral (hypoxia: 10% O2) and central chemoreflex (hypercapnia: 7% CO2) activation and acute stress (open-field exposure), were measured. As indicators of renal function, urinary protein (UPro) and creatinine (Ucr) levels were assessed. LPK rats had higher resting RSNA (1.2±0.1 vs. 0.6±0.1 µV, p<0.05) and MAP (151±8 vs. 97±2 mmHg, p<0.05) compared to Lewis. MAP was negatively correlated with Ucr (r=-0.80, p=0.002) and positively correlated with RSNA (r=0.66, p=0.014), with multiple linear regression modeling indicating the strongest correlation was with Ucr. RSNA and MAP responses to activation of the central chemoreflex and open-field stress were reduced in the LPK relative to the Lewis (all p<0.05). This is the first description of dual conscious telemetry recording of RSNA and MAP in a genetic rodent model of CKD. Elevated RSNA is likely a key contributor to the marked hypertension in this model, while attenuated RSNA and MAP responses to central chemoreflex activation and acute stress in the LPK indicate possible deficits in the neural processing of autonomic outflows evoked by these sympathoexcitatory pathways.